2022
DOI: 10.3390/vetsci9060294
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms, Gene Expression and Economic Evaluation of Parameters Associated with Mastitis Susceptibility in European Cattle Breeds

Abstract: The objective of this study was to explore single nucleotide polymorphisms (SNPs), gene expression and economic evaluation of parameters associated with mastitis susceptibility in Holstein and Brown Swiss dairy cows. Two hundred and forty Holstein and Brown Swiss dairy cows (120 cows of each breed) were used in this study. The investigated dairy cows in each breed were allocated into two equal-sized groups (60 cows each); mastitis tolerant and affected groups. PCR-DNA sequencing of SELL, ABCG2, SLC11A1, FEZL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…In addition, discovered a link between mastitis resistance and β-defensin gene polymorphisms ( Tolone et al ., 2016 ). Investigated SNPs in immunological ( SELL, ABCG2, SLC11A1 , and FEZL ) and antioxidant ( SOD1, CAT, GPX1 , and AhpC/TSA ) genes linked with mastitis risk in Holstein and Brown Swiss dairy cows were investigated ( Ateya et al ., 2022 ). The CD14 gene polymorphism and its link to mastitis was reported ( Kumar et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, discovered a link between mastitis resistance and β-defensin gene polymorphisms ( Tolone et al ., 2016 ). Investigated SNPs in immunological ( SELL, ABCG2, SLC11A1 , and FEZL ) and antioxidant ( SOD1, CAT, GPX1 , and AhpC/TSA ) genes linked with mastitis risk in Holstein and Brown Swiss dairy cows were investigated ( Ateya et al ., 2022 ). The CD14 gene polymorphism and its link to mastitis was reported ( Kumar et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2012 ) showed that mastitis-infected bovine mammary tissues had considerably greater levels of A2M mRNA and protein expression than did healthy tissues. According to Ateya et al . (2022 ), compared to tolerant cows, mastitic Holstein and Brown Swiss dairy cows exhibited significantly greater levels of SELL, SLC11A1 , and FEZL gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Using PCR-DNA sequencing for the immunological ( TLR4 , IL10 , TLR7 , NCF4 , TNF-α , and LITAF ) genes, there were changes in the nucleotide sequence between endometritis-affected cows and healthy ones. In addition, using PCR-DNA sequencing of immunological ( SELL , ABCG2 , FEZL , and SLC11A1 ) markers from the investigated Holstein and Brown Swiss dairy cows, nucleotide sequence alterations in the form of SNPs related to mastitis tolerance/susceptibility were found [ 44 ]. In cows, the LTF gene was linked to mastitis resistance [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and anatomy of cow udder has long been a subject for curious selection to improve the efficiency of milk production 5 . In addition, the teats of dairy animals are an important part of the udder, which is attached with a milking cluster and meantime, serves the roles of both a valve regulating the outflow of milk and of a natural barrier for exogenous infections 6 , 7 , teat shape and dimensions have no less emphasis in that regard 5 . Poor udder and teat conformations form a management challenge for dairy cow commercial producers.…”
Section: Introductionmentioning
confidence: 99%
“…Most dairy cattle breeding objectives worldwide have focused exclusively on production traits paying no attention to the severe deterioration in production properties caused, mainly by the unfavourable phenotypic and genetic correlations between linear type and milk production traits 37 . On the other side, there are genomic regions, that involve quantitative traits locus (QTLs), candidate genes and significant single-nucleotide-polymorphisms (SNPs) related to the udder and teat traits in dairy cattle 6,26,38 .The present study aimed to evaluate udder and teat characteristics in order to predict their relationship with milk production traits. The effects of udder shape, sire, parity, inbreeding and age at first calving on udder and teats measurements were also studied, with a spotlight on the genetic background of concerning traits.…”
mentioning
confidence: 99%